New research on pancreatic diseases at the Scientific Conference of the American Society of Gastroenterology “Digestive Disease Week 2016” in San Diego - Włodarczyk, Barbara; Małecka-Panas, Ewa (Lekarz POZ, 2016)
Diseases of the pancreas concern growing group of patients of GP. Initial diagnosis and early detection of acute pancreatitis (AP), chronic pancreatitis (CP) and pancreatic cancer (PC) enables the use of optimal treatment. Acute pancreatitis, due to its dynamic course, requires hospitalization. Keeping patients with CP is in the analgesic treatment and leveling disturbances of endo- and exocrine. The detection and treatment of PC at an early stage of its development improves the prognosis of these patients. These topics were discussed at the “Digestive Disease Week” (DDW), which is a prestigious, worldwide conference of the American Society of Gastroenterology, held regularly for many years. This year the venue of the meeting, which took place on 21-24 May 2016, was the Conference Center in San Diego.